Immmigration and Internal Mobility in Canada - Michel Beine; Serge Coulombe (Center for Economic Studies and ifo Institute (CESifo), 2014)
We analyze the impact of temporary foreign workers (TFWs) and permanent immigrants on interprovincial mobility in Canada. Particular attention is given to the Canadian program of TFWs that has intensified enormously over the last 30 years. Results of the empirical analysis are analyzed through the lens of a small theoretical model that incorporates a job-matching framework (Pissaridès, 1985, 2000) in a migration model à la Harris and Todaro (1970). We find that the inflow of TFWs into a given province tends to substantially decrease net interprovincial mobility. This is not the case, however, for the inflow of permanent immigrants selected through the Canadian point system. On average, each inflow of 100 TFWs is found to decrease net interprovincial migrants within the year by about 50, a number substantially higher than is present in existing literature. This number increases to 180 in the long run. The negative impact of TFWs is ascribed to the fact that TFWs are hired directly by employers, take vacant jobs, and display employment and participation rates of close to 100 per cent. Our paper suggests that, in general, the impact of immigration on labor market conditions depends critically on the way immigrants are selected.
Keywords: F22; J08; J29; J61; 330; internal mobility; immigration; foreign workers; displacement effect